FROM LITERACY TO LEADERSHIP: THE IMPACT OF FEMALE EDUCATION ON COMMUNITY DEVELOPMENT IN AFGHANISTAN - Sekandari, Oranos; Ghafori, Eidia; Ebrahimi, Mursal; Hajizadah, Negin; Tamanna, Quraishi; kakar, Wajia; Murady, Behishta (Yayasan Education and Social Center, 2025)
Female education is a critical factor influencing social and economic development in Afghanistan, yet numerous cultural, economic, and infrastructural barriers continue to limit girls’ access to education. This study explores the impact of female education on community development in Afghanistan, aiming to identify the key benefits, challenges, and effective strategies to enhance educational access for women. The research employed a quantitative methodology, collecting data through structured questionnaires distributed electronically via WhatsApp, email, and Facebook. A total of 110 female students aged 20 to 25 from Vision Higher Education and Research Institute, representing Medical, Computer Science, and Education faculties, participated in the study. The findings indicate that female education significantly contributes to leadership opportunities, poverty reduction, improved health outcomes, and economic growth within Afghan communities. However, cultural norms and traditions remain the most significant barriers, alongside security concerns and economic hardship. Participants identified building more schools, promoting e-learning, and community awareness programs as effective methods to improve female educational access. Additionally, technology plays a multifaceted role in facilitating flexible learning, expanding educational resources, and empowering women through entrepreneurial skill development. In conclusion, the study underscores that female education is a powerful catalyst for community development in Afghanistan but is constrained by complex social and infrastructural challenges. Addressing these obstacles requires comprehensive strategies that combine infrastructure development, technological integration, and socio-cultural engagement. These findings provide valuable insights for policymakers, educators, and stakeholders committed to advancing female education and fostering sustainable development in Afghanistan.